Recensioni - Comptes Rendus - Book Reviews - Francesca Piccioni; Federica Lazzerini; David Konstan; Francesca Boldrer; Antonello Orlando; Georgios Vassiliades (Ciceroniana On Line, 2017)
Book Reviews.